Dendronized polystyrene via orthogonal double‐click reactions. Issue 23 (25th September 2013) - Tonga, Murat; Yesilbag Tonga, Gulen; Seber, Gonca; Gok, Ozgul; Sanyal, Amitav
ABSTRACT Dendronized copolymers bearing two different dendrons as side chains have been synthesized using a modular orthogonal "double‐click" reaction based strategy. The orthogonality of the Huisgen‐type azide‐alkyne cycloaddition and the Diels–Alder reaction was utilized to attach different dendrons to the polymer backbone via the "graft‐to" strategy. First through third generations of polyaryl ether dendrons appended with an alkyne group and polyester dendrons possessing a furan‐protected maleimide group at their focal point were reacted with a styrene based copolymer containing azide and anthracene moieties as side chains. The efficiency and selectivity of the orthogonal dendronization of the copolymers were examined via various analytical methods such as 1H NMR spectroscopy, FTIR and gel permeation chromatography. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 5029–5037